Leadership with impact preparing health and human service practitioners in the age of innovation and diversity - Araque, Juan C. (Juan Carlos); Weiss, Eugenia L. (Oxford University Press, 2019)
"This book offers new ways of thinking and approaching complex problems through a conceptual and practical leadership approach founded on innovation and diversity. The I.D.D.E.A. Leadership Framework is introduced the goal of assisting health and human service practitioners with their design, implementation, and evaluation of innovative programs to help vulnerable populations and promote social change"--